2023
DOI: 10.3390/ma16237270
|View full text |Cite
|
Sign up to set email alerts
|

Endodontic Radiopacifying Application of Barium Titanate Prepared through a Combination of Mechanical Milling and Heat Treatment

Hsiu-Na Lin,
Wei-Wen Chen,
Chun-Chun Hsu
et al.

Abstract: Mineral trioxide aggregates (MTA) are commonly used as endodontic filling materials but suffer from a long setting time and tooth discoloration. In the present study, the feasibility of using barium titanate (BTO) for discoloration and a calcium chloride (CaCl2) solution to shorten the setting time was investigated. BTO powder was prepared using high-energy ball milling for 3 h, followed by sintering at 700–1300 °C for 2 h. X-ray diffraction was used to examine the crystallinity and crystalline size of the as-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 53 publications
0
1
0
Order By: Relevance
“…In the previous investigation, we demonstrated that BTO prepared using a combination of heat treatment and high-energy ball milling could be potentially used as a radiopacifier for mineral trioxide aggregates (MTAs). BTO-13 (mechanical milling for 3 h and heat treatment at 1300 °C for 2 h) was optimal and MTA-like cement mixed with 30% BTO-13 and solidified using 10% CaCl 2 solution exhibited the best performance for potential clinical application [ 21 ].…”
Section: Introductionmentioning
confidence: 99%
“…In the previous investigation, we demonstrated that BTO prepared using a combination of heat treatment and high-energy ball milling could be potentially used as a radiopacifier for mineral trioxide aggregates (MTAs). BTO-13 (mechanical milling for 3 h and heat treatment at 1300 °C for 2 h) was optimal and MTA-like cement mixed with 30% BTO-13 and solidified using 10% CaCl 2 solution exhibited the best performance for potential clinical application [ 21 ].…”
Section: Introductionmentioning
confidence: 99%